Evaluation of Pulmonary Function Tests Among Pregnant Women of Different Trimesters in Debre Berhan Referral Hospital, Shoa, Ethiopia - Amare YE; Haile D (Dove Medical Press, 2020)
Yosef Eshetie Amare,1 Diresibachew Haile2 1Department of Biomedical Sciences, Institute of Medicine and Health Sciences, Debre Berhan University, Debre Berhan, Ethiopia; 2Department of Physiology, College of Medicine and Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Yosef Eshetie AmareDepartment of Biomedical Sciences, Institute of Medicine and Health Sciences, Debre Berhan University, EthiopiaTel +251910966364Email yophy2006@gmail.comIntroduction: Pregnancy is characterized by a sequence of dynamic physiological changes that impact multiple organ system functions and is associated with various changes in pulmonary anatomy and physiology. Precise knowledge of the pulmonary function test parameters helps to understand and manage the course and outcome of pregnancy leading to safe delivery. It also helps to avoid misdiagnosis and unnecessary interventions. The aim of this study was to evaluate the effect of normal pregnancy on pulmonary function tests among pregnant women in Debre Berhan Referral Hospital, Ethiopia.Methods: A total of 176 study participants (first, second, and third trimester; and control) were involved under a comparative cross-sectional study design and convenience sampling technique. Anthropometric data, oxygen saturation of arterial blood, and pulmonary function tests were measured. Data were tabulated and statistically analyzed using SPSS version 20.0 statistical software. Means of all parameters were compared using one-way ANOVA followed by Tukey’s post hoc multiple comparison test. Statistical significance was preset at a p-value of less than 0.05.Results: Mean of FVC for the controls, first, second, and third trimesters was 2.59 ± 0.26, 2.13 ± 0.15, 1.93 ± 0.27, and 1.90 ± 0.11 liters, respectively. Except for FEV1%, the mean values of FVC, FEV1, PEFR, and FEF 25– 75% in the pregnant group (all the three trimesters) were significantly decreased from the controls (P< 0.05). Strong negative correlation was seen between SaO2 and RR (r= − 0.865; P < 0.01). As the pregnancy progressed from first to the third trimester, dynamic pulmonary function tests (FVC, FEV1, FEF25-75%, and PEFR) were dropped and the respiratory rate increased.Conclusion: The results had shown the tendency of obstructive pattern while pregnancy becoming advanced. We have observed also a remarkable decline of SaO2 in pregnant women that might be counterbalanced by raised respiratory rate.Keywords: pregnancy, high altitude, FVC, trimester, oxygen saturation